(untitled) (Mongolian Journal of Agricultural Sciences, 2025)
This study evaluated the chemical composition, sensory attributes, fatty acid profile, and microbiological quality of pasture-raised goat offal soup and mushroom-enriched products. Product formulations were optimized through sensory evaluation. Trained panelists rated the offal soup containing 8% liver as the most palatable (93/100), while the formulation with 50% mushrooms (F3) achieved the highest acceptability. The offal soup and mushroom-enriched products contained 68.0 vs. 70.6% moisture, 18.5 vs. 19.2% protein, 7.7 vs. 2.9% fat, 1.3 vs. 1.2% ash, 4.5 vs. 6.0% carbohydrates, and 424 vs. 670 mg/100 g salt, respectively. Total saturated fatty acids (SFA) accounted for 54.73% in the soup and 30.2% in the mushroom product; monounsaturated fatty acids (MUFA) were 42.28% vs. 32.1%, and polyunsaturated fatty acids (PUFA) were 3.62% vs. 37.3%, respectively. The predominant fatty acids were oleic (39.6%), stearic (27.9%), and palmitic (21.9%) in the soup, and linoleic (34.2%), oleic (30.0%), and palmitic (17.2%) in the mushroom product. Microbiological counts remained below 10³ CFU/g during a six-month storage period, confirming product safety. These findings demonstrate that both products are nutritionally balanced, microbiologically stable, and represent sustainable food innovations for the meat industry. Moreover, it can be products that meet the healthy and natural food choices prioritized by modern consumers.